Value of Information and Decision Pathways: Concepts and Case Studies - Glynn, Pierre D.; Rhodes, Charles R.; Chiavacci, Scott J.; Helgeson, Jennifer F.; Shapiro, Carl D.; Straub, Crista L. (Frontiers in Environmental Science, 2022)
Information arises from the structuring of observations and data and plays a key role in decision-making. The collection, dissemination, and use of information has monetary and non-monetary costs (e.g., competition for attention) and necessitates trade-offs. Understanding the benefits of having information (i.e., the value of information, VOI), including resulting societal outcomes, is useful to information producers/funders and decision makers. We explore, including through a number of use cases, how information (e.g., geospatial information) is valued and incorporated in decisions and actions related to managing natural resources, environments, and the impacts of natural and anthropogenic hazards. We discuss the nature of information and how it relates to models (conceptual, mental, scientific), beliefs, knowledge, and economic analyses. VOI approaches and behavioral factors that potentially affect information use and value are summarized. A framing of information and VOI through the context of data to decision pathways (DDPs) is presented, illustrating the benefits of information, and human and societal challenges encountered in valuing and using it. We present approaches to overcome these challenges. Our transdisciplinary analysis concludes with a summary of critical issues affecting DDPs and VOI, and suggestions for improving both economic analyses and the actionability and use of information.